Comprehension‐Based Versus Production‐Based Grammar Instruction: A Meta‐Analysis of Comparative Studies. Issue 2 (10th March 2013) - Shintani, Natsuko; Li, Shaofeng; Ellis, Rod
Abstract : This article reports a meta‐analysis of studies that investigated the relative effectiveness of comprehension‐based instruction (CBI) and production‐based instruction (PBI). The meta‐analysis only included studies that featured a direct comparison of CBI and PBI in order to ensure methodological and statistical robustness. A total of 35 research projects in 30 published studies were retrieved. The studies were coded for three types of effect sizes: comparative, absolute, and pre‐to‐post change. The comparative effect sizes were used in a subsequent moderator analysis to test the impact of two mediator variables—CBI with and without Processing Instruction and PBI involving text creation versus text manipulation. The results showed that (1) overall, both types of instruction had large effects on both receptive and productive knowledge; (2) for receptive knowledge, CBI had a greater effect than PBI when the acquisition was measured within one week but the difference diminished in the delayed tests (i.e., posttests administered between 1 week and 75 days after the treatment); (3) for productive knowledge, CBI and PBI had similar effects in short‐term measurement but PBI was more effective in the delayed tests; and (4) the initial advantage found for CBI was largely due to Processing Instruction. We discuss the theoretical and pedagogical significance of these findings.